An Analaysis of Category Shift and Its Equivalence in Tourism Promotion Video Subtitles - Puspita Sari, Sintya; Erfiani, Ni Made Diana; Kamayana, I Gusti Nyoman Putra (LPPM Universitas Dhyana Pura, 2025)
This study aims to identify the types of category shift defined by Catford theory (1965) and Nidaâ€™s for translation equivalence (1964). The descriptive qualitative method was used to analyze the data. This study used a secondary source from four videos. First, Badung Heaven of Dream, second, Pantai Melasti were posted in Jegeg Bagus Badung YouTube Channel. Third, Pungin puspa, and fourth, A Story of Sacred Bond from West Bali were posted on Jegeg Bagus Bali YouTube Channel. This study analyzed words, phrases, clauses, terms, and sentences. Total data were 33 data, which analyzed qualitatively.Â The analysis showed that there were four types of category shift. They were Structure shift (17), Class shift (1), Unit shift (10), and Intra-system shift (5). This study also found two types of translation equivalence. Namely Formal equivalence (21) and dynamic equivalence (12). The most dominant types of category shift that found is structure shift and the most dominant equivalence that found is formal equivalence.